Python framwork and libraries for DSP GUI demos - Nguyen, Thanh Tung (2017)
The development of the Graphical User Interfaces (GUIs) has been found to be an essential component in learning of Digital Signal Processing (DSP) topics. In this project, we will be developing Python Framework and Libraries to develop DSP GUI demos. DSP GUI demos are software learning tools which helps students to understand DSP and/or Digital Communication concepts. The aim of the Framework to integrate these Python GUI apps such that when the user runs the main code, the system will detect all the available Python GUI apps. The user can also add new Python GUI apps from other courses. Generally, this framework is a one-stop platform that can facilitate the various Python GUI apps from the different courses available. Also, to make this set of learning tool more versatile, we want the next user to be able to add new Python GUI apps without ever changing the main code. The structure of the one-stop platform was implemented by using an XML-based architecture. Libraries are created to help user build the apps with ease. With the help of these libraries, the Python GUI apps are created short and more organized. These libraries contain basic widgets, helping tools such as plotting, animation, and layout customization. This report will include the implementation of the Framework and describing the features of the Python GUI Libraries that have been developed. At the end of this project, several DSP Python GUI apps were developed to demonstrate the libraries and the framework. There will be examples for user on how to create Python GUI apps using the library and integrate into the framework